2010
DOI: 10.5539/ijbm.v5n11p106
|View full text |Cite
|
Sign up to set email alerts
|

A Profile Analysis of the Customers of Islamic Banking in Peshawar, Pukhtunkhwa

Abstract: The call of giving all subscribers a greater opportunity in the Islamic banking systems is well documented in the
literature of the first decade of this millennium. Many banks and financial institutions across the world have
attempted to implement programs aiming at increasing the customer’s involvement in terms of investment and
financing with varying degrees of success. The study describes the attributes and profiles of the Islamic banking
subscribers.
A list of attributes and charac…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
3
11
2
Order By: Relevance
“…For instance, prior studies have revealed that intentions to seek high rate of return influence customers to pursue services of Islamic banks (Farooq, Ahmad and Jamil, 2010). On the other hand, results of this study also align with the findings of Al-Ajmi et al (2009) who suggest that religious motivations of customers are the major factors that influence them to adopt Islamic banking services.…”
Section: 4supporting
confidence: 81%
See 3 more Smart Citations
“…For instance, prior studies have revealed that intentions to seek high rate of return influence customers to pursue services of Islamic banks (Farooq, Ahmad and Jamil, 2010). On the other hand, results of this study also align with the findings of Al-Ajmi et al (2009) who suggest that religious motivations of customers are the major factors that influence them to adopt Islamic banking services.…”
Section: 4supporting
confidence: 81%
“…For instance, in the case of profits, both entrepreneur and investor would share profits with each other in an agreed proportion. On the contrary, in case of losses, all the capital losses would be borne by the individual who provides capital whereas the entrepreneur would only borne the losses of time and labor put into a project (Farooq, Ahmad and Jamil, 2010). Consequently, fair distribution of wealth is achieved through this system that s the essence of Islamic financial principles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they stressed that the positive relationship between service quality and customer satisfaction is stronger for IBs than for CBs. In the same year Farooq, Ahmad & Jamil (2010) also conducted a research with the aimed of describing the attributes and profiles of Islamic banking subscribers by statistically testing a sample of 942 subscribers and users of Islamic banks in Pakistan and they empirically suggested that the regulators of Islamic banking should concentrate on the socio-demographic factors when it comes to establishment of a new branch. They therefore emphasised that the aspiration and preferences of the educated class shall be taken into consideration and products and services should be designed in such a way to cater for the needs of the subscribers.…”
Section: Literature Reviewmentioning
confidence: 99%